EFFECTS OF REGIONAL GEO-POLITICAL CHANGES ON PAKISTAN – RUSSIA RELATIONS - Saeed, A. (Farabi Journal of Social Sciences, 2023)
This article aims to analyze how, throughout the Cold War era, Pakistan did not cultivate strong ties with Russia. It was the international structure that compelled Pakistan to join the Western bloc, addressing the security and economic needs of a newly born state. Similarly, the USSR’s support for India led to strategic imbalance in the South Asian region. However, global politics is dynamic, not static. The 21st century, especially post-9/11, has transformed the global political arena. Contemporary global politics is witnessing new alliances; today, Pakistan is looking towards the East while India’s focus is towards the West. Geo-political and geo-strategic changes are reshaping global politics. This study aims to highlight the changing geo-political landscape of the region, the factors responsible for policy shifts, responses to the new global geo-strategic scenario, and how these changes have helped bring the former Cold War rivals, Russia and Pakistan, closer. Gradually, Russia and Pakistan are strengthening diplomatic ties, with Pakistan securing Western support. While Pakistan has signed military cooperation deals with the USA and other European countries, it is also compelled to reassess its foreign policy weaknesses and forge closer ties with Russia and other regional states. This shift is driven by a need to build trust and move away from the hegemonic designs of Pakistan and the US in the South Asian region. Keywords: Geo- politics, regional security, Pakistan, Russia, Cold War, multi-polarity.